Strategies for MSMEs to Face Economic Crisis in An Islamic Perspective - Ismail, Ammar (Teunuleh Publisher, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the main pillars of the Indonesian economy, but at the same time they are the most affected sectors in the economic crisis situation. This article aims to examine the adaptive strategies used by MSMEs in dealing with economic crises and analyze them through the perspective of sharia economic values. This study uses a qualitative approach with a literature study method, with secondary data obtained from various scientific literature, policy reports, and official publications. The results of the study show that the strategies that are widely applied by MSMEs include cost efficiency, product diversification, business digitalization, and strengthening social networks. These strategies are considered effective in increasing business resilience. From a sharia perspective, the success of the strategy is also determined by its conformity with the principles of justice, honesty, benefit, and the prohibition of usury and exploitative practices. Although the principles of Islamic economics offer significant moral and social strength, their implementation still faces challenges, such as low sharia literacy, limited access to sharia financing, and suboptimal policy support. Therefore, the integration of sharia values in MSME strategies needs to be strengthened through a cross-sectoral approach to build a resilient and equitable business ecosystem.